Ritual da mídia: os elementos rituais e sua aplicação pelos meios de comunicação de massa - Magossi, Priscila Gonçalves (2008)
The research is dedicated to the study and applications of some ritual elements in the mass media, as an attempt to fulfill the emptiness of existence, occasioned by the arrival of consciousness in the primordial man. Justification for this topic is based on the perception that the primitive man, with his mythic thoughts, and the modern man, straight thoughts formulated, have the same collective ritual dimensional base. Ritual must be read as a group of actions defined by their symbolic importance to a specific society. The actions and symbols aren't freely chosen by individuals, they are imposed by an external source. For the primordial man, the source is the ceremonial priests. For the modern man, the source is the influence of mass media. Showing how media uses the archetypical and sacred aspect of the ritual, manipulating its core for their own needs and satisfaction: fascination, enchantment, infiltration and stereotyping. By the Cultural Semiotic prism, the thesis aspires to contribute to studies and cultural communication, aiming for the rescue of complexity in the means of communication. How primitive rituals formats still survive in modern media, albeit in a saturated way, is the question this study addresses. Adopted methodological procedure was a research of qualitative character, involving analysis and bibliographical survey. As the theorical board of references are the authors B. Cyrulink, D. Kamper, E. Morin, H. Pross, I. Bystrina, J. Hillman, K. Lorenz, M. Berman, M. S. Contrera, N. Baitello Jr., N. Sevcenko, V. Flusser, V. Romano e Z. Bauman. The conclusion is that, even if banalized and distorted, the principles of symbolic reorganization of the ritual still exert considerable influence in the media and in the mindset of the modern man